Ratio of Th17/Treg and Disease Activity in Systemic Lupus Erythematosus - Yuliasih Yuliasih (Caspian Journal of Internal Medicine, 2019)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by T-cells imbalance. There are ongoing controversies about the role of specific T-helper cell subsets and their cytokines. The study aimed to confirm the disturbance of Th17/Treg ratio in SLE patients. Methods: Subjects were SLE patients who met the American College of Rheumatology 1997 criteria. Disease activity assessment was measured by SLAM index. Th17 and Treg level was measured by flow cytometry. Th17 level was evaluated as CD4+L17 whilst Treg as CD4+Foxp3+. Final result is stated as Th17/Treg ratio. Results: Thirty female subjects with active SLE had mean SLAM Score of 29.3±3.88, C3 level 25.2 (6-59.5), C4 level 15.25 (5-54.3), ESR 62.1±37.85, CRP 30.16±59.45, and anti-dsDNA 155.32±186.10. Higher Th17 level was found in SLE patients compared to healthy subjects (30.09 pg/ml vs 13.01pg/ml; 12.60% vs 0.91%). However, it did not correlate to disease activity (p>0.05; r=-0.28). Regarding Treg level, there was no significant difference between active SLE and healthy subjects (12.85 vs 11.05 pg/ml; 9.57% vs 2.05%). Treg level negatively correlated to SLE disease activity (p<0.01; r=-0.73). Th17/Treg ratio was 3.28±2.22% and it positively correlated to SLE disease activity (p<0.01; r=0.78). Conclusion: Th17/Treg ratio is positively correlated with disease activity. Th17 level is elevated but not correlated with disease activity. Decrease of Treg level is not significant though correlated with disease activity in SLE patients.